2018
DOI: 10.1186/s12870-018-1511-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dehydrin protein, CdDHN4-L and CdDHN4-S, and their differential protective roles against abiotic stress in vitro

Abstract: BackgroundDehydrins play positive roles in regulating plant abiotic stress responses. The objective of this study was to characterize two dehydrin genes, CdDHN4-L and CdDHN4-S, generated by alternative splicing of CdDHN4 in bermudagrass.ResultsOverexpression of CdDHN4-L with φ-segment and CdDHN4-S lacking of φ-segment in Arabidopsis significantly increased tolerance against abiotic stresses. The growth phenotype of Arabidopsis exposed to NaCl at 100 mM was better in plants overexpressing CdDHN4-L than those ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 47 publications
4
18
0
Order By: Relevance
“…The results show that all four proteins possess similar CD spectra; a large negative minimum ellipticity is observed at ~200 nm, and a small negative signal is seen after 212 nm (Figure 1(c)), suggesting that these proteins are largely disordered when alone in solution. These results agree with what has been reported for other LEA proteins 21,45–47 …”
Section: Resultssupporting
confidence: 93%
“…The results show that all four proteins possess similar CD spectra; a large negative minimum ellipticity is observed at ~200 nm, and a small negative signal is seen after 212 nm (Figure 1(c)), suggesting that these proteins are largely disordered when alone in solution. These results agree with what has been reported for other LEA proteins 21,45–47 …”
Section: Resultssupporting
confidence: 93%
“…In this study, it was found that DHNs not only act as drought-resistant protein, but also interact with FK506 binding protein in the nucleus and acts as regulatory protein for drought tolerance by regulating the ABA responsive signaling pathway (Tiwari et al, 2019). DHNs have been recognized as molecular protectors for functionality of some proteins such as lactate dehydrogenase and malate dehydrogenase in response to environmental stresses, as supported by previous studies (Zhou et al, 2017;Lv et al, 2018). Misfolding of proteins that are toxic to plants is triggered by drought stress, so protein quality control is critical to plant quality.…”
Section: Dhns and Other Proteins' Interactionssupporting
confidence: 65%
“…The DSI gene, VrDHN3, was induced under drought and combined stresses and during drought recovery in leaves of IC333090 and petioles of IC488526. DHNs are unfolded proteins functioning as protective molecular chaperones for enzymes and phospholipids, enhancing plant tolerance to abiotic stresses (Lv et al 2018). Expression of DHN3 and DHN44 were highly correlated with yield in barley under drought stress (Park et al 2006).…”
Section: Discussionmentioning
confidence: 99%